Analysis of Economic Growth and Investment on The Welfare of The Community of Central Java - Sugeng Haryono; Nurlaela Nurlaela (Fakultas Pendidikan Ekonomi dan Bisnis, 2022)
The author's purpose in researching is to find out more about economic growth on the welfare of the people in Central Java. To find out whether investment has an effect on the welfare of the people in Central Java. This study uses a quantitative method, with multiple linear regression analysis using panel data of 350 samples, taken from 29 districts, 6 cities in Central Java with a total sample of 10 years (from 2011 to 2020). The independent variables in this study are economic growth and investment, human welfare as the dependent variable. The result of this research is that Economic Growth and Investment simultaneously have a significant effect on Human Welfare, this shows that these two variables need to be considered by local governments. The implementation of the results of this study is that local governments must always maintain the regional economy by helping and supporting the marketing of domestic products so that they are well known to foreign countries and can export them, so that investors will have more confidence and commitment to the area.